Microfracture Arthroscopy Efficacy In Treatment Of Articular Cartilage Insult Of Knee - Mohamed Baqir Alshara (مجله كليه طب الكندي, 2018)
Background: The treatment of articular cartilage defects is one of the most clinical challeng for orthopedic surgeons. Articular cartilage is a highly organized tissue with complex biomechanical properties and substantial durability. However, it has a poor ability for healing, and damage from trauma or degeneration can result in morbidity and functional impairment. debilitating joint pain, dysfunction, and degenerative arthritis                                                                           Objectives: The purpose of study is to show effectiveness of micro fracture arthroscopy as a method of treatment for such problem .